The impact of health insurance on health sector indicators in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aimed to analyze the relationship between financial technology dimensions (rational intelligence, data warehouse, technological control, direct analytical processing, data mining) on the one hand as an independent variable, and the financial performance of insurance companies operating in the city of Lattakia on the other hand.The study relied on the descriptive approach as a general method for the study, and it relied on the questionnaire as a tool for data collection. It also relied on the soft random sampling method, where 89 questionnaires were distributed for analysis, and the spss program version No. 20 was used to analyze the data, researches have used simple linear correlation, multiple regression, and test differences for one sample.The study reached a set of results, the most important of which are:• Lack of financial technology dimensions in insurance companies operating in Lattakia.• There is a medium strong direct relationship between the availability of a data warehouse and the financial performance of the studied companies.• There is a strong direct relationship between (data mining, technological control, rational intelligence, direct analytical processing) and the financial performance of the studied insurance companies.